Enhanced extraction efficiency of bioactive compounds and antioxidant activity from Hippophae rhamnoides L. by-products using a fast and efficient extraction method - Tsui, Daniel C.; Wink, Michael (Separation science and technology, 2017)
In this study, a novel method named high-speed homogenization coupled with ultrasound-assisted extraction (HSH-UAE) followed by high-performance liquid chromatography (HPLC) was employed and investigated for the extraction and determination of main flavonoids rutin, quercetin-3-O-glucoside, quercetin, kaempferol and isorhamnetin from Hippophae rhamnoides L. by-products. Optimal conditions for HSH-UAE, proposed by the single factor and the Box-Behnken design (BBD) tests coupled with response surface methodology (RSM), were 68% ethanol concentration, ultrasonic power 250 W, homogenate speed 9000 rpm, liquid/solid ratio 22 mL/g and extraction time 12 min. The extraction yields of five main flavonoids were significantly improved by HSH-UAE than UAE and high-speed homogenization-assisted extraction (HSHAE). Furthermore, the antioxidant activity of HSH-UAE extracts was assessed by 1,1-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing/antioxidant power (FRAP) assays with IC50 value of 0.091 mg/mL and 2.837 mmol FeSO4/g DW. Good linear ranges were obtained for five main flavonoids in the range of 2.5-500 μg/mL with the coefficient higher than 0.99. The recoveries of the five flavonoids were in the range of 97.87-99.26%. The limit of detection (LOD) and the limit of quantification (LOQ) for the main flavonoids were within the ranges of 0.28-0.46 and 0.89-1.74 μg/mL, respectively. The present results showed that the proposed method HSH-UAE could be developed as a fast and efficient method for extracting the active ingredients from medical edible plant materials for potential application.
Gesehen am 03.08.2017